Keberkesanan pembakaran udara berperingkat dalam mengurangkan emisi dari pembakar berbahanapi gas - Mohd. Jaafar, Mohammad Nazri; Sulian, Mohd Sharul (The Institution of Engineers, Malaysia, 2005)
Combustion process from a gas burner tends to emit emissions containing several different pollutants such as NOx, CO, CO2 etc. These emissions must be reduced as they are harmful towards living things. Due to this, a study on the burner performance is very essential to ensure that the burner is able to operate efficiently and producing low emissions level. An experiment has been performed by regulating the airflow rates at 7, 8, 9, 10 and 12 g/s. This experiment also involved injecting secondary air to study the emission reduction. Results obtained showed that the optimum burner operation is at equivalence ratio of 0.86 and at 17.69 kW.